Self-assembled nitrogen-doped fullerenes and their catalysis for fuel cell and rechargeable metal–air battery applications. Issue 22 (13th April 2017) - Noh, Seung Hyo; Kwon, Choah; Hwang, Jeemin; Ohsaka, Takeo; Kim, Beom-Jun; Kim, Tae-Young; Yoon, Young-Gi; Chen, Zhongwei; Seo, Min Ho; Han, Byungchan
Abstract : Formation and catalysis of self-assemble nitrogen-doped fullerenes as non-precious catalyst. Abstract : In this study, we report self-assembled nitrogen-doped fullerenes (N-fullerene) as non-precious catalysts, which are active for the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER), and thus applicable for energy conversion and storage devices such as fuel cells and metal–air battery systems. We screen the best N-fullerene catalyst at the nitrogen doping level of 10 at%, not at the previously known doping level of 5 or 20 at% for graphene. We identify that the compressive surface strain induced by doped nitrogen plays a key role in the fine-tuning of catalytic activity.